Impact of Physical Activity on Weight Loss during Intermittent Fasting in Adults - Hafsa Tahir, Wajeeha Waqar, Khadija Ali, Kaynat Fatima, Sania Maqbool, Hassaan Umar, Umar Bacha, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity is increasing rapidly in our country leading to many chronic diseases and health related issues. Intermittent fasting proves to be beneficial in treating obesity in other countries but have not been much researched in Pakistan. If proves valuable IF can prevent adults from falling prey to crash diets and unhealthy diet practices which promotes bad health. Aims: To evaluate the impact of IF on weight loss in adults, to evaluate impact of physical activity on weight loss during IF and to check weather calorie restriction is necessary or not for weight loss. Methods: We did an experimental study on a sample of 30 adults, which followed IF for 1 month. They were provided with online counseling and guidelines to follow. Moreover, they were divided into two groups A and B one with physical activity of 20 min walk and one without it to see the impact of physical activity on IF. Plus an online survey was created after 1 month to know how much weight they lose and how they feel about this regimen. SPSS V21 was the tool used to analyze the data Results: IF is a beneficial practice to treat obesity. However Physical activity increases the impact of weight loss however people also reduced weight without any activity. There were no major side effects. People find it unique and easy to follow. They were prone to follow it in future too for weight loss purposes. Practical implication: By the help of this study we will get to evaluate the impact of IF on health parameters in Adults. IF will be easy to follow and will show long term effects without showing any rebound effects. Moreover, we need more data in this particular field for appropriate use and application of this regimen in Asian households and cultural aspects. It can promote public health in Pakistan. Conclusion: The research concludes that intermittent fasting is helpful in reducing weight but it is more effective in males as compared to females. Two groups were made A group was doing IF with exercise while the B group only do Intermittent fasting, more weight loss has been seen in A group as compared to group B. Keywords: Intermittent fasting (IF), physical activity, weight loss, adults.